52.1k views
4 votes
Find f(x) and g(x) so the function can be expressed as y = f(g(x)). y=
(2)/(x^2)+3

User Rgettman
by
4.8k points

1 Answer

3 votes

Answer:

One possible answer is:

f(x) = (2/x) + 3 and g(x) = x².

Explanation:

Explanation:

We are to write this equation as y = f(g(x)). This means we want it to be a composite of functions; in f(x), we take the value of g(x) and use in place of x.

If we let g(x) = x², this means everywhere we see an x in f(x), we will replace it with x². To make our equation y = 2/x² + 3, working backward we would substitute x for x²; this would give us f(x) = 2/x + 3.

User Michael Tsang
by
5.1k points